Forms of Hadrah Art Presentation in the Procession of Wedding Party in Dusun Sawah Village - Shella Meisaliara; Wimbrayardi (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2023)
This study aims to find and describe the form of presentation of the Hadrah Parade art in Dusun Sawah Village using a qualitative research method with a descriptive analysis approach.  To collect data the researchers conducted observations, interviews, and documentation.  The object of this research is the Hadrah Art of the Procession and this research shows how the form of the presentation of the Hadrah art in the procession of the procession in Dusun Sawah Village is displayed at weddings.  In the wedding ceremony, it was found that in terms of the art form, the Hadrah procession used a tambourine as a musical instrument and the lyrics used came from the Al-Barzanji book entitled Sidal Habi, Salabat Laila and Ya Rasulullah while the presentation of Hadrah Art was usually shown at 08.00  WIB, in the afternoon after the midday prayer at 13.00 WIB or in the afternoon at 16.00 WIB and played by 15-35 people.  Hadrah art is entertainment for the people in Dusun Sawah Village and establishes a closer sense of kinship between communities.